Economic analysis : theory and application - Charles S. Maurice; Phillips, Owen R.; Ferguson, C. E. (Charles E.). (Homewood, Ill. : R.D. Irwin, 1982)
"This textbook is designed for undergraduate courses in basic microeconomics- the theory of value and distribution. Over the past several years have noticed that students in economics courses have become increasingly interested in applications of theories they learn in class. Moreover, to give students more practice in problem solving".
Rev. ed. of: Economic analysis / C.E. Ferguson. 3rd. ed. 1978.
Includes bibliographical references and index.
English text.
Keywords: Microeconomics